2015
DOI: 10.1007/s00467-015-3154-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated uric acid and obesity-related cardiovascular disease risk factors among hypertensive youth

Abstract: Background Uric acid (UA) is associated with high blood pressure in adolescents and left ventricular hypertrophy (LVH) and cardiovascular disease (CVD) in adults. We sought to determine if UA is independently associated with CVD risk factors and left ventricular mass (LVM) over time in hypertensive youth. Methods One-year prospective observational study of hypertensive children aged 3-19 years. Cross-sectional and longitudinal associations of serum UA with CVD risk factors and LVM were explored. Results At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Two recent studies of adolescents included in NHANES 1999-2000 and a small study conducted in Italy found that elevated UA levels were associated with higher BP. 395 -397 In the Italian study and in another US study of youth with obesity and HTN, 397,398 elevated UA was also associated with other markers of CV risk. These findings suggest that the measurement of UA levels may best be viewed as 1 component of CV risk assessment, especially in those with obesity.…”
Section: Uric Acidmentioning
confidence: 99%
“…Two recent studies of adolescents included in NHANES 1999-2000 and a small study conducted in Italy found that elevated UA levels were associated with higher BP. 395 -397 In the Italian study and in another US study of youth with obesity and HTN, 397,398 elevated UA was also associated with other markers of CV risk. These findings suggest that the measurement of UA levels may best be viewed as 1 component of CV risk assessment, especially in those with obesity.…”
Section: Uric Acidmentioning
confidence: 99%
“…We generally consider that young persons constitute one of multiple populations at risk for primary hyperuricemia [19] and a recent report by Reschke et al [20] indicated an increased incidence of hyperuricemia among adults aged 3 to 19 years. The most common clinical symptom of hyperuricemia is gouty arthritis, so the majority of patients are treated; furthermore, hyperuricemia may also cause cardiovascular disease, cerebrovascular disease, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Each medical statistical method has its scope of application and its confounding factor control strategy; if these are ignored during the scope of its application, erroneous results may be obtained, such that the effectiveness of the research will be questioned. 4 – 12…”
Section: Discussionmentioning
confidence: 99%